Mapping the darkness : the visionary scientists who unlocked the mysteries of sleep - Miller, Kenneth (Journalist) (Hachette Books, 2023)
Journalist Kenneth Miller weaves science with history to tell the story of four outsider academics who carried the study of sleep from fringe discipline to mainstream obsession. In the 1920s Nathaniel Kleitman founded the world's first dedicated sleep lab, with breakthrough experiments in 1938. Kleitman mentored Eugene Aserinsky who discovered REM sleep, and William Dement, who became known as the father of sleep medicine. Dement, in turn, mentored Mary Carskadon, who uncovered an epidemic of sleep deprivation among teenagers. -- From book jacket flap.